Peningkatan Literasi Teknologi Guru melalui Pelatihan E-Evaluation Berbasis HOTS di SMAS Muhammadiyah Kota Bima: Dampak pada Efektivitas Evaluasi Pembelajaran - Irawati, Ika; Annisah, Annisah; Ilyas, Ilyas; Meirawan, Deddy (Jurnal Gema Ngabdi, 2024)
The implementation of E-evaluation based on Higher Order Thinking Skills (HOTS) in private high schools remains limited. Observations from the Community Service Team revealed several issues, including the minimal use of E-evaluation in Muhammadiyah High Schools. Interviews with the principal and several teachers indicated that evaluations are still predominantly paper-based. In 4.0 era, it is essential for both teachers and students to adapt the technological advancements, especially in the evaluation process. E-evaluation serves as an effective tool for assessment at the high school level. The goals of this initiative are to: 1) enhance the technological skills of teachers at partner private schools, 2) improve teachers' understanding of E-evaluation, 3) develop HOTS-based E-evaluation products, and 4) increase teachers’ knowledge about crafting questions that promote Higher Order Thinking Skills. The methods used include presentations, demonstrations, and hands-on practice. The proposed steps for working with teachers are: 1) FDG, 2) training and mentoring, 3) monitoring, and 4) evaluation. The outcomes of this activity include: (1) 90% teacher participation, (2) 80% teachers grasping how to formulate HOTS-based questions, (3) 90% understanding the use of E-evaluation, (4) 90% of students gaining familiarity with courses in Human and Computer Interaction, Teaching Strategies, and Learning Evaluation, (5) the creation of an E-evaluation module/guidebook, (6) certificates for teachers who develop E-evaluation questions, (7) visual materials such as posters, (8) published articles in the Abdi Insani journal, (9) media coverage of activities in online platforms, and (10) activity videos uploaded to the STKIP Taman Siswa YouTube channel. So, the practical significance for teachers is improving the quality of education using E-evaluation Technology in Private schools